복강경을 이용한 요근 농양의 치료 - 홍창화(Chang-Hwa Hong); 배상호(Sang-Ho Bae); 박종석(Jong-Seok Park); 정현우(Hyun-Woo Jung); 장병웅(Byung-Woong Jang) (The journal of the Korean Orthopaedic Association, 2013)
요근 농양은 그 발생 빈도가 낮으며, 치료가 적절치 못한 경우 사망률이 높다. 또한 이의 치료에 있어서도 그 해부학적 위치가 후복막의 깊은 곳에 위치하여 수술적 도달이 쉽지 않다. 현재 컴퓨터 단층촬영을 이용한 배액관 삽입과 함께 항생제를 투여함으로써 좋은 치료 결과를 얻고 있는 상태이다. 이러한 치료에도 효과가 없을 시 수술적 치료가 필요하다. 저자들은 요근 농양에 대하여 복강경을 이용한 직접 배액을 시도함으로써 좋은 결과를 얻을 수 있었기에 이를 문헌 고찰과 함께 보고하는 바이다. Psoas abscess is a rare and high mortality disease if there is no appropriate treatment. The surgical approach of psoas abscessis very difficult because psoas muscle is anatomically located within retroperitoneum. Recently, computed tomography guidedpercutaneous catheter drainage with proper antibiotic therapy has shown good results. If this therapy fails to resolve the psoasabscess, surgical treatment may be necessary. We experienced two cases of psoas abscess resolved by surgical drainage usinglaparoscopy. We report two successful results with relevant literatures. KCI Citation Count: 0